Effects of social hierarchy in primiparous and multiparous goats on nursing behavior during lactation - García-Cázares, Andrea; Cano-Suárez, Paolo; Terrazas-García, Angélica (Frontiers in Ethology, 2025)
IntroductionGoats are gregarious animals with a social organization differentiated by their stratification into defined social ranks. Relatively little is known about whether these social relationships affect the behavioral activity of mothers and offspring during lactation. Therefore, the objective of this study was to evaluate the effect of social hierarchy in primiparous and multiparous goats on nursing behavior during lactation.MethodsForty-seven multiparous and 25 primiparous French Alpine and Toggenburg goats were used. They were weighed, their body condition was evaluated during the second half of pregnancy and lactation, and the weights of their kids were measured during two months of age. To evaluate the hierarchy, a success index was calculated by recording the antagonistic interactions between animals in the second and last weeks of lactation. Furthermore nursing activities were recorded approximately 14 days postpartum and weekly until day 55 of lactation. The following behaviors were recorded: frequency of nursing episodes, episodes in which the mother accepted or rejected, and the duration of each nursing episode.ResultsBoth primiparous and multiparous goats had the highest percentage at the medium dominance level (65%). This was significantly higher than those at the low dominance level (20%) and the high dominance level (15%, P< 0.001). Body weight and body condition scores were higher in goats with a high dominance than in those with a medium or low social hierarchy (P< 0.05). The body weights of the kids were not affected by the dominance of their mothers (P > 0.05). There were no differences among the three dominance levels in the duration of episodes, episodes accepted or rejected, or the number of total nursing episodes observed during lactation (P > 0.5).ConclusionRegardless of parity, the maternal hierarchy level significantly affected productive parameters in goats, but not offspring growth or nursing behavior during lactation.